The Role of Topal Husein Pasha in the Vienna War (1683-1699) (Prilozi za orijentalnu filologiju, 2019)
This paper considers the role of Topal Husein Pasha in the Vienna War (1683-1699). This Ottoman vizier served as the vali (governor) of Bosnia from mid-1687 until early 1691. This was the most dramatic stage of the Vienna war – the time of the great Habsburg offensive, which was expected to be a definitive push of the Ottomans away from the Balkans. Nevertheless, Bosnia remained under the rule of the Sultan, primarily thanks to the agile governor, Topal Husein Pasha, his local commander (ćehaja) Mehmed Bey (Korča), and the primarily local military forces. They also contributed considerably to the Ottoman counter-offensive, with the army led by the Grand Vizier Mustafa Pasha Ćuprilić regaining much of the previously lost territories. This paper examines the origin and background of Husein Pasha, as well as the reasons for his removal from office in the eyelet of Bosnia.